Kualitas Layanan Sebagai Determinan Kepuasan Mahasiswa Politeknik Ketenagakerjaan di Masa Pandemi COVID-19 - Christina Amanda Savitri; Ni Luh Putu Nia Anggraeni; Dony Firman Santosa (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The success of a university can be seen from students’ satisfaction with the services provided. Students’ satisfaction is also the key to students’ loyalty to university. This research aims to measure the level of students’ satisfaction on the service quality of Politeknik Ketenagakerjaan (Polteknaker), to identify service quality attributes that need to be improved and maintained at the Polteknaker, to analyze the effect of Polteknaker service quality on student satisfaction, and to analyze the effect of satisfaction on the loyalty of Polteknaker students. There are 100 students of Polteknaker were involved in this research. The data were collected through questionnaires and analyzed using the Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and Structural Equational Modeling-Partial Least Square (SEM-PLS). Based on the student satisfaction index (CSI) result, the quality of Polteknaker services as a whole is 64.39% which shows students feel quite satisfied with the provided services. The results of the IPA shows that the most important indicators that should be improved are reliability, responsiveness, and assurance. Based on the results of SEM-PLS, the responsiveness and empathy have a positive and significant impact on students’ satisfaction, consequently resulting in students’ loyalty. Keywords: CSI, Empathy, IPA, Responsiveness, SEM-PLS